Strategy for improving sugar palm agroindustry institutions in South Tapanuli - Pulungan, Sutan; Harahap, Angelia Utari; Aswan, Novita; Nasution, Zakiyah (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2024)
One of the palm oil derivative products that has the potential to grow in southern Tapanuli was the processing of sap or brown sugar which has been produced by palm trees through rural industrialization using palm sugar processing technology. In developing palm oil farming in South Tapanuli, it was important to prepare institutions through science and technology with structural equation models. The objective of this research was to develop an agro-industry development strategy to improve the institution of palm trees. This research was observation respondents totaling 112 brown sugar producers. The result was to produce a statement through the perceptions of sugar palm farmers in Tapanuli, that sugar palm farmers in Tapanuli support the role of women in managing palm agro-industry institutions and agree that women will be able to take a role in resolving conflicts in sugar palm agro-industry institutions. Sugar palm farmers in Tapsel agree that there will be many differences of opinion from people who will manage the sugar palm agro-industry and differences of opinion will affect the existence of the sugar palm agro-industry in Tapanuli Selatan.